(untitled) (lectio difficilior, 2021)
We know of six men who committed suicide in the Hebrew Bible and of no woman; we know of one man and one woman who committed suicide in archaic Greek epic. In spite of these small number, one reads in secondary literature of the Greek’s fondness of suicide or the peaks of mythical suicide. After methodological considerations why and how to compare archaic Greek literature and texts of the Hebrew Bible, I show how suicide was written in Greek myth in later times; the earliest extant literary form of Greek myth in archaic epic shows little interest in women’s death; texts of the Pentateuch, Judges, Samuel and Kings also show little interest in women’s death. Women in both literatures, Greek and Hebrew, are women in relationship, the most prominent relationship is motherhood, especially being mother of a son. I think, the lack of interest in women’s death together with the focus on motherhood are two reasons why no woman’s suicide is mentioned in the Hebrew Bible.